Regenerative Medicine for Congenital Diaphragmatic Hernia: Regeneration for Repair - De Coppi, Paolo; Deprest, Jan (European Journal of Pediatric Surgery, 2012)
Regenerative medicine has developed recently as a new field of science aiming at restoring organ and tissue damage through the use of autologous constructs. Cellular therapies and relatively simple tissue engineering reconstructions have recently been successfully applied into patients. For babies born with congenital diaphragmatic hernia, regenerative medicine may play a role both in developing a myogenic patch capable of restoring muscle function and promoting regeneration of hypoplastic lungs that characterised those patients. The latter is particularly attractive because it may change the long-term outcome of those children. We aim here to discuss recent advancement in the field, looking in particular at the future clinical prospective of those exciting therapeutic strategies.
Keywords: congenital diaphragmatic hernia; regenerative medicine; newborns